Using the E-Module in the Firefighting Course to Increase Cadets’ Motivation - Sutiyo Sutiyo; Fitri Masito; Wildan Nugraha; Yeti Komalasari; Christina Brown (Journal of Innovation in Educational and Cultural Research, 2024)
The Firemanship course is one of the mandatory courses taught to pilot cadets. As part of one of the capabilities of Airport Rescue and Fire Fighting (ARFF), the firemanship course provides pilot cadets with the ability to handle fire incidents at airports. The application of technology in learning firemanship courses has not been widely practiced by aviation education institutions. Using e-modules can increase aviation cadets’ abilities, including learning motivation. In this research, the e-module for the firemanship course was created using the ADDIE method. The result is an increase in understanding scores and the ability to increase the learning motivation of pilot cadets. The increase can be seen from the minimum score of the pre-test, which is 1.6, increasing to 3.2 in the post-test. The maximum score in the pre-test of 2.2 increases to 3.7 in the post-test. The overall average score also increases in the pre-test from 1.96 to 3.53 in the post-test. This research also shows that there are differences in the understanding scores of Palembang Aviation Polytechnic cadets in firemanship courses. Learning using e-modules also provides a difference in value even though it is not significant. This adds to the literature on the application of ADDIE in making e-modules which are also effectively used in firemanship courses in particular.